Application of Continuous Wound-Infusion Catheters in Lung Transplantation: A Retrospective Data Analysis - Lenz, Nils; Hirschburger, Markus; Roehrig, Rainer; Menges, Thilo; Mueller, Matthias; Padberg, Winfried; Mann, Valesco (The Thoracic and Cardiovascular Surgeon, 2017)
Background Lung transplantation is the only treatment option for many patients with end-stage pulmonary disease. Therefore, postthoracotomy pain therapy is of vital interest. Thoracic epidural analgesia (EPI) is the “gold standard” for postthoracotomy pain, but especially in lung transplantation contraindications, and potential infectious complications limit its advantages. Under these circumstances surgically placed postthoracotomy catheter-assisted continuous paravertebral intercostal nerve block (PVB) could be of advantage.Methods We performed a retrospective cohort study of patients who underwent lung transplantation between 2005 and 2012. Groups were defined according to the type of postoperative pain therapy: PVB, EPI, and SYS (systemic analgesia). Total 44 patients were eligible.Results Postoperative opioid requirement of the PVB and EPI group was comparable and less than that of the SYS group. Patients of the PVB group were weaned earlier from mechanical ventilation after lung transplantation.Conclusion The potency of postoperative pain therapy of EPI and PVB seemed to be comparable and superior to SYS. Considering the risks and benefits, PVB could be a better choice than EPI for postthoracotomy pain therapy, especially in lung transplantation.
Keywords: anesthesia (includes related subject matter); transplantation; lung; intensive care